2000
DOI: 10.1046/j.1365-2168.2000.01383-13.x
|View full text |Cite
|
Sign up to set email alerts
|

Current practice in the management of acute cholecystitis

Abstract: AIMS: Several recent papers have advocated emergency cholecystectomy for patients with acute cholecystitis, stating that it is safe, cost effective and leads to less time off work. This study was designed to assess current practice in the management of acute cholecystitis in the UK. METHODS: A postal questionnaire was sent to 357 consultant surgeons who were thought to be involved in a general surgical on-call rota, to ascertain their current management of patients with acute cholecystitis. Replies were receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…Only 15-20% of surgeons have adopted the policy of urgent cholecystectomy during the index admission. 29,30 The perceived risk of higher complications (particularly bile duct injury and conversion rates) may be responsible for the unpopularity of early laparoscopic cholecystectomy. Other possible contributory factors could be the delays caused by availability of emergency operating lists and the radiology investigations, which essentially means that the surgeons miss the 'window of opportunity' for surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Only 15-20% of surgeons have adopted the policy of urgent cholecystectomy during the index admission. 29,30 The perceived risk of higher complications (particularly bile duct injury and conversion rates) may be responsible for the unpopularity of early laparoscopic cholecystectomy. Other possible contributory factors could be the delays caused by availability of emergency operating lists and the radiology investigations, which essentially means that the surgeons miss the 'window of opportunity' for surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous postal questionnaire to the general surgeons who were thought to be involved in the general surgical on-call rota, Cameron and colleagues 28 reported that only 12% of the surgeons treated their patients by emergency cholecystectomy whenever possible. In the current survey, the proportion of early operators, albeit higher (20%), has remained low.…”
Section: Management Of Acute Cholecystitismentioning
confidence: 99%
“…The hospital stay was shorter in the early group. In another prospective trial, the conservative treatment failed completely in 14.3% of patients who had to undergo emergency operations and 33% had to be operated earlier than planned [75] .…”
Section: Lc Vs Ocmentioning
confidence: 99%
“…Min et al [73] defi ned it if two or more of the clinical and operative fi ndings were positive: fever 1 37.5 ° C, right upper abdominal pain with tenderness 1 48 h, gallbladder wall 1 4 mm, adhesion to an adjacent organ and infl ammation of the gallbladder serosa [74] . Cameron [75] …”
Section: Current Status Of Laparoscopic Therapy For Acute Cholecystitismentioning
confidence: 99%